Identity and security in the competition for power in Israel - Fernando Navarro Muñoz (Revista CIDOB d'Afers Internacionals, 2012)
The language of security has immediate effects; it constitutes a speech act. By using the language of security, an actor reclaims the use of extraordinary media in order to deal with the threats that it presents to public opinion; this is called securitisation. However, security is not always objective, and sometimes the interests of specific sectors in their competition for power are concealed behind the argument of general interest. Starting from a concept of enlarged security, we propose a review of the concept of societal security as described by Barry Buzan and Ole Waever, which suggests a security based on the identity of communities, and we do so by focusing on the experience of Israel, where security and identity go hand-in-hand in the discourse. We also add a proposal from the sociology of power: the discourse of security is just another resource in the competition for power.